ANALYSIS OF ANTEPARTUM HEMORRHAGE AND ASSOCIATED RISK FACTORS FOR MATERNAL AND NEONATAL OUTCOMES (The Research of Medical Science Review, 2025)
This study involves pregnant women and their babies: it goes on to examine the prenatal, maternal and neonatal features that give rise to Antepartum Haemorrhage (APH).The study shows notable results related to maternal  age, education background, number of births, obesity and pregnancy outcomes. Age- related risks were shown, with 36% of the participants under 20 years of age and 33% over 35.Maternal educational level was uneven. Those with college education made up 24% of the participants, There were 15% who didn't even graduate from elementary school. Obesity was common among the patients, with 57% obese (more than one year).This represented for 35% of pregnancies being premature and reinforced the need to improve prenatal care. Total sicknesses such as diabetes and hypertension were common. 55% of participants had diabetes while 47% experienced hypertension in the pregnancy. POST  operative proportions were also large, with 38% (see FlG.1).A number of risk factors such as previous uterine scars, gestational hypertension, multiple childbearing, and advanced motherhood (over 35) were very common in this group. The study further identifies significant placental problems like placenta previa, abruption, and accreta, which present substantial risks to both mother and new born child. Large parts of maternal outcomes involved carrying out cesarean sections, removing the uterus, as well as post delivery anemia as a result of blood loss. Neonatal outcomes show high rates of low birth weight, stillbirths and suffocation at birth. This is a severe challenge for health. The study calls for antenatal monitoring targeted to identified patients, interventions early on and better new- born care.